Fundamentals of entrepreneurship (ENT300) : Romantika Bridal Boutique / Fuad Hafeez Abdullah ... [et al.] - Abdullah, Fuad Hafeez; Ambrose, Inez Sute; Cowboy, Jasmeen; Abdul Aziz, Nurshafiqah; Pa-Un, Jenylia (2014)
Romantika Bridal Boutique is partnership is in form of enterprise which consist of five members. We had chosen this kind of business because it show the equality and no one will discriminate as the profits and losess are equally divided in the end of the accounting period. Thus, the partnership is a perfect option to be taken because the shareholders will always sháring ideas and knowledge in order to gain profit and archieve high productivity.